Assessment of planning target volume margins in 1.5 T magnetic resonance‐guided stereotactic body radiation therapy for localized prostate cancer. Issue Volume 6:Issues 2(2022) (12th May 2022) - Yang, Bin; Yuan, Jing; Poon, Darren M.C.; Geng, Hui; Lam, Wai Wang; Cheung, Kin Yin; Yu, Siu Ki
Abstract: Objective: We aimed to determine the planning target volume margins applicable to magnetic resonance‐guided stereotactic body radiation therapy (MRgSBRT) of localized prostate cancer on a 1.5 T MR‐Linac. Methods: A total of 10 patients with low‐ to intermediate‐risk prostate cancer were retrospectively enrolled. All patients received five‐fraction MRgSBRT treatments, and underwent daily endorectal ballooning and bladder control. Five patients were implanted with the hydrogel rectal spacer. Three MR scans at each fraction were acquired to evaluate the intrafractional prostate motion. The required planning target volume margin was determined using the van Herk margin recipe based on direct MR‐MR prostate registration. The set‐up margin for localization using bony anatomy was also estimated. Results: The mean and standard deviation of translational displacement in left‐right (LR), superior‐inferior (SI), and anterior‐posterior (AP) directions were –0.3 ± 0.7, 2.0 ± 1.5, and 1.4 ± 1.1 mm, respectively. Planning target volume margins over the MRgSBRT fraction duration were 2.8 (LR), 5.3 (SI), and 3.9 mm (AP). Set‐up margins were estimated to 2.6 (LR), 3.3 (SI), and 3.3 mm (AP). Prostate motion increased considerably with treatment duration. Adapt‐to‐position had smaller intrafractional motions than adapt‐to‐shape. The rectal spacer insignificantly (p > 0.1) reduced the prostate motion in SI and AP. Conclusion: Online workflow efficiency enhancement and intrafractional motion monitoring are vital for planning target volume margin reduction and precision enhancement in MRgSBRT. Abstract : Three sets of MR scans (pre‐treatment, position verficiation, and post‐treatment) at each fraction were acquired for each patient to evaluate the time‐dependent intra‐fractional prostate motion. The required PTV margin for MRgSBRT was determined using van Herk margin recipe based on direct MR‐MR prostate registration. The setup margin for localization using bony anatomy was also estimated. In conventional IGRT based on bony anatomy match, PTV margin includes both setup margin and internal margin. By facilitating the direct target match, the setup margin can be eliminated for margin reduction in MRgSBRT. PTV margin estimated in this study is applicable to online adaptive MRgSBRT .